2018
DOI: 10.17957/ijab/15.0543
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nutrition and Distribution in Plants of Different Thai Rice Varieties

Abstract: Rice grain yield benefits from silicon (Si) accumulation in sufficient concentration in the plant, but too much Si in the husk and straw can impede their usefulness as biofuel and animal feed. This study consisted of four experiments. The first experiment evaluated genotypic variation in Si distribution in different parts of the rice grain from farmers' fields in northern Thailand, parts of grain to compare tall plant type and semi-dwarf varieties. The result showed that there were significant differences amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…Previous studies have reported that the expression of Lsi6 level was affected by Si supply in maize leaves and it was upregulated by addition of Si 27 . The nearly 30% higher Si concentration in the husk of CNT1 than PTT1 when grown in the field 28 and the significantly higher Si concentration in the husk of CNT1 than PTT1 in +Si in the present study together suggest that Si may be a yield‐limiting factor in spikelet formation. It is well established that spikelet formation is a key yield‐determining step in rice 2,29 .…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Previous studies have reported that the expression of Lsi6 level was affected by Si supply in maize leaves and it was upregulated by addition of Si 27 . The nearly 30% higher Si concentration in the husk of CNT1 than PTT1 when grown in the field 28 and the significantly higher Si concentration in the husk of CNT1 than PTT1 in +Si in the present study together suggest that Si may be a yield‐limiting factor in spikelet formation. It is well established that spikelet formation is a key yield‐determining step in rice 2,29 .…”
Section: Discussionsupporting
confidence: 70%
“…Si is transported to different parts of the rice plant largely along the transpiration stream, 34–36 with a transport gene responsible for loading Si into the grain and presumably the husk identified at the node beneath the panicle 15,37 . Compared with the Si concentration in field‐grown CNT1 and PTT1, 28 the Si concentrations in different plant parts of the same rice genotypes grown in solution culture in this experiment were very low. As 5% Si in the shoots at maturity is considered the critical level for deficiency, 2 Si was likely to be limiting for the rice plants in the present study, including those in +Si, where the shoots’ Si was less than 2%.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The experiment was arranged in a factorial completely randomized design with three independent replications. The three modern rice varieties used in this experiment were Chainat 1 (CNT1), Pathumthani 1 (PTT1), and Khao Dawk Mali 105 (KDML105), selected with respect to their husk Si concentration, with 8.7%, 7.1%, and 6.7% dry weight of husk Si concentration, respectively [ 43 ]. Plants were grown in 15 cm-diameter pots containing 4 kg soil.…”
Section: Methodsmentioning
confidence: 99%